Contribution of cuproptosis and immune-related genes to idiopathic pulmonary fibrosis disease - Jin, Chengji; Li, Jia; Li, Qiaoyu; Zhang, Lipeng; Zheng, Shaomao; Feng, Qiong; Li, Yongjie; Zheng, Yu; Nie, Qiuli; Liang, Jin; Wang, Jing (Frontiers in Immunology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a degenerative respiratory condition characterized by significant mortality rates and a scarcity of available treatment alternatives. Cuproptosis, a novel form of copper-induced cell death, has garnered attention for its potential implications. The study aimed to explore the diagnostic value of cuproptosis-related hub genes in patients with IPF. Additionally, multiple bioinformatics analyses were employed to identify immune-related biomarkers associated with the diagnosis of IPF, offering valuable insights for future treatment strategies.MethodsFour microarray datasets were selected from the Gene Expression Omnibus (GEO) collection for screening. Differentially expressed genes (DEGs) associated with IPF were analyzed. Additionally, weighted gene coexpression network analysis (WGCNA) was employed to identify the DEGs most associated with IPF. Ultimately, we analyzed five cuproptosis-related hub genes and assessed their diagnostic value for IPF in both the training and validation sets. Additionally, four immune-related hub genes were screened using a protein–protein interaction (PPI) network and evaluated through the receiver operating characteristic (ROC) curve. Lastly, single-cell RNA-seq was employed to further investigate differential gene distribution.ResultsWe identified a total of 92 DEGs. Bioinformatics analysis highlighted five cuproptosis-related genes as candidate biomarkers, including three upregulated genes (CFH, STEAP1, and HDC) and two downregulated genes (NUDT16 and FMO5). The diagnostic accuracy of these five genes in the cohort was confirmed to be reliable. Additionally, we identified four immune-related hub genes that demonstrated strong diagnostic performance for IPF, with CXCL12 showing an AUROC of 0.90. We also examined the relationship between these four genes and immune cells. CXCL12 was significantly negatively associated with neutrophils, while CXCR2 was associated exclusively with neutrophils, consistent with our single-cell sequencing results. CTSG showed a primarily positive association with follicular helper T, and SPP1 was most strongly associated with macrophages. Finally, our single-cell sequencing data revealed that in patients with IPF, CXCL12 was highly expressed in the endothelial cell subset (ECs), while SPP1 exhibited high expression in multiple cellular populations. The expression of the CTSG showed statistically significant differences in monocyte macrophages.ConclusionThe research methodically depicted the intricate interplay among five cuproptosis-related genes, four immune-related hub genes, and IPF, offering new ideas for diagnosing and treating patients with IPF.